2016
DOI: 10.1038/nrurol.2016.89
|View full text |Cite
|
Sign up to set email alerts
|

The role of the prostate in male fertility, health and disease

Abstract: Ejaculation is a synchronized cascade of events that has the ultimate goal of activating sperm and enabling them to reach an egg for fertilization. The seminal plasma contains a complex mixture of fluids that is secreted from the testes, epididymis and male accessory glands. The prostate gland has a pivotal role in this process, as prostatic fluid enriched in Zn(2+), citrate and kallikreins is crucial for the molecular synchronization of the functional cascade triggered by ejaculatory stimuli. The prostate is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
119
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(129 citation statements)
references
References 66 publications
(87 reference statements)
3
119
0
7
Order By: Relevance
“…In addition, they have shown that prostate inflammation induces chronic pelvic pain development and has deleterious effects on semen quality compromising male fertility [6,25]. However, compelling available data from studies in patients are limited [6,25,26]. In the present study, we provide novel evidence indicating that Th1 and Th17 self-reactive immune responses specific to PAg are detected in a considerable proportion of patients with CP/CPPS, which may be responsible for the observed inflammation of the male genital tract.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…In addition, they have shown that prostate inflammation induces chronic pelvic pain development and has deleterious effects on semen quality compromising male fertility [6,25]. However, compelling available data from studies in patients are limited [6,25,26]. In the present study, we provide novel evidence indicating that Th1 and Th17 self-reactive immune responses specific to PAg are detected in a considerable proportion of patients with CP/CPPS, which may be responsible for the observed inflammation of the male genital tract.…”
Section: Discussionmentioning
confidence: 54%
“…Such animal models mirror most features of human CP/CPPS and have shown that prostate inflammation induction is mediated by T-cell responses specific to PAg. In addition, they have shown that prostate inflammation induces chronic pelvic pain development and has deleterious effects on semen quality compromising male fertility [6,25]. However, compelling available data from studies in patients are limited [6,25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At copulation, a mixture of cauda epididymal spermatozoa and accessory gland secretions is ejaculated into the female reproductive tract. The accessory gland secretions mainly come from the seminal vesicles (SV), prostates, bulbourethral gland (also known as “Cowper's gland”), and urethral glands . Specifically, men ejaculate 3–3.5 mL of semen into the female reproductive tract, which is mainly composed of secretions from SV (1.5–2.0 mL), prostates (0.5 mL), and bulbourethral gland and urethral glands (0.1 mL) .…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the seminal vesicles, prostate, testes, and epididymides are the major secretory origins and account for approximately 65%, 25%, and 10%, respectively, of the semen volume (Drabovich et al, 2014). Some seminal proteins have tissue specificity: Seminal vesicles mainly secrete semenogelins and fibronectin (Lilja et al, 1987), the epididymis secretes clusterin (Han et al, 2012), the prostate secretes kallikreins (Verze et al, 2016), and the bulbourethral glands secrete mucinous proteins (Boursnell et al, 1970).…”
Section: Introductionmentioning
confidence: 99%